2012
DOI: 10.1080/10937404.2012.736856
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives for in Vitro Risk Assessment of Multiwalled Carbon Nanotubes: Application of Coculture and Bioinformatics

Abstract: Nanotechnology is a rapidly expanding field with wide application for industrial and medical use; therefore, understanding the toxicity of engineered nanomaterials is critical for their commercialization. While short term in vivo studies have been performed to understand the toxicity profile of various nanomaterials, there is a current effort to shift toxicological testing from in vivo observational models to predictive and high-throughput in vitro models. However, conventional monoculture results of nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 145 publications
0
43
0
2
Order By: Relevance
“…The use of the co-culture model which allows for the study of epithelial and endothelial cellular communication within the alveolar-capillary unit, offers an advantage over mono-culture cell models commonly used in nanotoxicology studies. It is worth nothing that a comparative study recently performed by our group showed that the in vitro alveolar-capillary co-culture model correlates with in vivo results more closely than a mono-culture model upon treatment with multi-walled carbon nanotubes (MWCNT) (Snyder-Talkington BN, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…The use of the co-culture model which allows for the study of epithelial and endothelial cellular communication within the alveolar-capillary unit, offers an advantage over mono-culture cell models commonly used in nanotoxicology studies. It is worth nothing that a comparative study recently performed by our group showed that the in vitro alveolar-capillary co-culture model correlates with in vivo results more closely than a mono-culture model upon treatment with multi-walled carbon nanotubes (MWCNT) (Snyder-Talkington BN, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…De hecho, la mayoría de las propiedades típicas que los caracteriza (pequeño tamaño en al menos una dimensión entre 1-100 nm, su gran área superficial por peso y su reactividad) son precisamente las propiedades que los hacen tecnológica-mente tan valiosos y estas son probablemente las razones para sus efectos dañinos potenciales [65,66,67].…”
Section: Desafíos De La Industria Químicaunclassified
“…Generation of cytotoxicity due to the interaction of metal oxide nanoparticles with the biological system is still unclear [9]. There are several studies that have reported cytotoxicity of ZnO nanoparticles in various cell lines.…”
Section: Introductionmentioning
confidence: 99%